Emerging Diseases Structure, Controversy and Change in the Scientific Constitution of Disease Patterns - Döring, Martin; Kollek, Regine 1950- (VerKörperungen/MatteRealities - Perspektiven empirischer Wissenschaftsforschung, 2018)
Hypotheses about diseases and their causes are often controversial and contested. Concepts of diseases have always been subject to modification and disagreement. At the core of these debates about ailments are controversies among scientists, clinicians and patients who debate causes, transmission routes and contributing factors. All these processes produce re-categorisations in different fields of research and sometimes lead to the social emergence of disease concepts - compared to the scientific and epidemiological concept of disease aetiology.In this edited volume scholars from a variety of disciplines analyse disease concepts empirically and study underlying processes of emergence, contestation and change in the biomedical sciences